INFLUENCE OF FUNCTIONALIZED MULTI-WALLED CARBON NANOTUBES ON FILTERABILITY AND MECHANICAL PROPERTIES OF RAYON NANOCOMPOSITE FILAMENTS - Holia Onggo; Rike Yudianti; Endang Ruchiat (JURNAL SELULOSA, 2013)
Carbon nanotube-rayon composite filaments was fabricated by spinning and coagulation of the mixture of 100mL functionalized carbon nanotube dispersion (containing 0.72 g FCNT) and cellulose xanthate in NaOH solution using viscose process. In the process, CNT was functionalized using mixture of acidic solution ( H2SO4/HNO3, 3:1 v/v). Influence of functionalized (FCNT) and non-functionalized carbon nanotubes (nFCNT) on the fabrication of rayon nanocomposite filament was studied. Physical and morphological properties of the nanocomposite filaments were characterized by single filament tenacity tester, photo micrograph, scanning electron microscope (SEM) and transmission electron microscope (TEM). Filterability and mechanical properties of FCNT-rayon nanocomposite filament greatly improved by reducing clogging constant from 1689 to 153 and increasing tenacity from 2.72 to 3.01 g/denier and decreasing elongation from 57.1 to 36.5% respectively compared with those of nFCNT-rayon nanocomposite filament.Keywords: functionalized multi-walled carbon nanotubes, nanocomposite filament, mechanical properties, filterability, dispersion  ABSTRAKRayon nanocomposite filaments telah dibuat melalui proses pemilinan (spinning) dan koagulasi (coagulation) dari campuran 100 mL larutan functionalized carbon nanotube dispersion (FCNT=0,72 g), selulosa santat dalam larutan NaOH melalui proses viskosa. CNT di functionalisasi (FCNT) menggunakan campuran larutan asam (H2SO4/HNO3, 3:1 v/v). Pengaruh fungsionalisasi CNT pada pembuatan rayon nanocomposite filaments dipelajari dengan cara membandingkannya dengan CNT tanpa fungsionalisasi (nFCNT). Sifat fisik dan morfologi dari rayon-nanocomposite filaments dikarakterisasi menggunakan tenacity tester, photo micrograph, scanning electron microscope (SEM) dan transmission electron microscope (TEM). Viskosa FCNT memiliki daya saring (Kw) cukup baik yaitu 155, sedangkan viskosa nFCNT  memiliki daya saring 1689 (tidak baik). Kekuatan mekanik dari FCNT-rayon nanocomposite filaments berturut turut adalah 3,01 g/denier (tenacity), dan 36,5% (elongation), lebih baik dibandingkan dengan nFCNT-rayon nanocomposite filament: 2,72 g/denier (tenacity) dan 57,1% (elongation).Kata kunci: fungsionalisasi multi-walled carbon nanotubes, rayon-nanocomposite filament, sifat mekanik, daya saring, dispersi